The developement of novel scaffolds for tissue engineering with a range of structural and mechanical properties - Haugh, Matthew George (Trinity College (Dublin, Ireland). Department of Mechanical and Manufacturing Engineering, 2009)
Tissue engineering (or regenerative medicine) is defined as the application of scientific principles to the synthesis of living tissues using bioreactors, cells, scaffolds, growth factors, or a combination (Rose and Oreffo, 2002). One of the principal methods in tissue engineering involves the use of a porous scaffold to support and guide synthesis of a 3D tissue or organ (Sachlos and Czernuszka, 2003). Collagen-Glycosaminoglycan scaffolds have found success in several clinical applications of tissue engineering (Yannas et al., 1989, Chamberlain et al., 1998).
Keywords: Mechanical Engineering, Ph.D.; Ph.D. Trinity College Dublin